A comparison of some methods for estimating the Weibull distribution parameters - Alsaidi Altaher , Abdslam Suliman , Nuri Ali Jamela Abo-Neran; Iman Abo-Grarah (Journal of Pure & Applied Sciences, 2018)
This study aims to compare the practical performance of three methods to estimate the parameters of Weibull distribution. These methods are: the method of maximum likelihood, the method of moments and the method of Ordinary least squares. Simulation experiments have been conducted for evaluation purposes under different real distribution parameters and different sample sizes.Results showed that the method of maximum likelihood seems to bemore appropriate to estimate the unknown parameters for large sample size whereas the method of moments and the method of Ordinary least squares can be used for small sample sizes.